Korpus teori pembentukan kontrak - Azimon Abdul Aziz,; Sakina Shaik Ahmad Yusoff, (Fakulti Undang - Undang, 2009)
Symbolically, contract resembles the human pulse. Our daily life depends on contracts. Various aspects of life depend on contracts to arrange and facilitate daily activities, whether from the aspects of social, politics or economics. Awareness on the importance of contracts existed as early as the 13th century. Contract theories existed with natural law as its underlying cause. Philosophers propounded their own theories on contract. Consequently, ideologies developed centred around the questions of the relationship and impact of contract on society and life. The basic principles of the law of contract derived from the basic theories of contract and contract formation are seen to be challenged by the introduction of various forms and types of modern transactions invading the world. Applying a pure legalistic analysis, based purely on literature review, this article analyses the theoretical corpus underlying contract development and formation